Journal of Orthopaedic and Sports Physical Therapy (Journal of Orthopaedic & Sports Physical Therapy)
The Journal of Orthopaedic and Sports Physical Therapy (JOSPT) is the official journal of the Orthopaedic Section, American Physical Therapy Association, and the Sports Physical Therapy Section, American Physical Therapy Association.